Прогнозирование надежности рам тележек вагонов электропоездов - Жовдак, В. А.; Белоцерковский, Александр Борисович (НТУ "ХПИ", 2005)
The problem of definition of reliability characteristics of bogie frames of transit vehicles taking into account the chance of loading and characteristics of fatigue resistance is considered. Prognostication of reliability is conducted on the basis of solution of statistical dynamics problem. The methods of solution and results of computational investigation are given
Keywords: железнодорожный транспорт; предел выносливости; эксплуатация вагонов метрополитена; амплитуды напряжений